Some engraved gems from Ammaia - Graça Cravinho (Pallas, 2010)
The article presents stones from Roman rings that belonged to Doctor Delmira Maças’s archeological collection. All were discovered in irrigation canals in the fields in which the Roman city of Ammaia, Portugal, was located (to day S. Salvador de Aramanha, Alentejo). Comparisons are made with similar objects to be found in the corpus of the stones of Roman rings in Portugal.